The Quality of Life of Women Divorced due to Domestic Violence - Dian Nur Latifah; Sheilla Varadhila Peristianto (Developmental and Clinical Psychology, 2024)
The Indonesian government defines domestic violence as any act of violence against a person, particularly women, that results in physical, sexual, psychological, or economic harm or suffering within the home. This encompasses threats of violence, coercion, and the deprivation of freedom. The high prevalence of domestic violence and the negative impacts that occur on victims of domestic violence make problems related to domestic violence a significant problem that affects the quality of life. This research employs a qualitative research method with a case study approach, with the objective of elucidating the quality of life of women who are divorced as a result of domestic violence. The findings of this study indicate that the participants' physical condition deteriorated following divorce, increasing their susceptibility to disease. Furthermore, the psychological condition of the participants was found to be poor, their spiritual quality was low, and their social relationships declined. However, following the commencement of employment, women who were divorced due to domestic violence were ultimately able to enhance their quality of life, including attaining greater financial stability and psychological well-being. This was characterized by a lack of fear and depression. Furthermore, there was a discernible improvement in their quality of life in social relationships, manifested in the form of numerous interpersonal connections